Usage of Non-Pharmacologic Methods on Postoperative Pain Management by Nurses: Sample of Turkey. - Yaban, Zuleyha Sımsek (International Journal of Caring Sciences, 2019)
Background: At the postoperative period, postoperative pain one of the most important patient complains is an acute pain starting with surgical trauma, lessening gradually and ending by the tissue recovery. The essential aim in nursing care of postoperative pain is to do patient assessment with nursing approaches. Furthermore pharmacologic and non-pharmacologic nursing interventions that included individual plan are to implementation and evaluation. Purpose: The purpose of this literature review which non-pharmacological methods can be used by nurses to cope with post-operative pain in Turkey. Method: The databases of Turkish Medical Index, Google Akademik, YOK Thesis Search, Pubmed, Google Scholar, EBSCO Host, Web of Science were scanned to reach the studies. It was determined that 35 studies were in conformity with the inclusion criteria. Findings: In postoperative pain control, nonpharmacologic pain control methods can be used to increase the effect of analgesics, in case of insufficient effect of analgesics, or when analgesics cannot be used. Among nonpharmacologic postoperative pain control methods, transcutaneous nerve stimulation, application of hot and/or cold compresses, relaxation exercises, music therapy, massage, reflexology, aromatherapy rarely used in postoperative pain control but hypnosis, reiki, yoga and acupuncture can not be implemented by nurses in Turkey. Conclusion: It is seen that majority of the studies conducted on nonpharmacologic methods in Turkey were masters or doctoral theses. These methods can not be performed by nurses working at the hospitals in Turkey. The reasons non-pharmacological methods were practiced less frequently by nurses were insufficient number of nurses, patients' reluctance about pain control, lack of time, and lack of information about pain control. In accordance with these results it is recommended to give more space for teaching the non-pharmacological methods that can be applied for pain management and legal regulations can be improved.